Clinical efficacy of retreatment of daratumumab‐based therapy (D2) in daratumumab‐refractory multiple myeloma. (21st February 2023) - Abdallah, Al‐Ola; Mahmoudjafari, Zahra; Ahmed, Nausheen; Cui, Wei; Shune, Leyla; McGuirk, Joseph; Mohan, Meera; Mohyuddin, Ghulam Rehman; Afrough, Aimaz; Alkharabsheh, Omar; Atrash, Shebli
Abstract: Daratumumab demonstrates activity as a single agent and in combination with either immunomodulatory agents (IMiDs) or proteasome inhibitors (PIs) in relapsed refractory multiple myeloma (RRMM). However, little is known about the benefit of daratumumab retreatment in daratumumab‐refractory MM. This study aimed to analyze the clinical efficacy of daratumumab‐based retreatment (D2) in patients who are daratumumab refractory MM. Retrospectively, we identified 43 RRMM patients from a single‐center database review. The median age was 65 years, 42% patients had high‐risk cytogenetics, and 23% had an extramedullary disease, while the median time between D2 and prior daratumumab was 1 (0.25–39) month. All D2 patients received combination therapy with either pomalidomide, carfilzomib, bortezomib, or lenalidomide. The response rate, median progression‐free, and overall survival were 49%, 7.97 and 32.6 months, respectively. Our study raises the possibility of re‐utilizing daratumumab in combination with different classes of anti‐myeloma drugs to generate responses in RRMM patients who are daratumumab‐refractory.